THE RELATIONSHIP OF ANEMIA DURING PREGNANCY TO THE INCIDENCE OF PARTUS WITH THE COMPLICATION OF ASPHYXIA INNEWBORN BABY AT NUR MALINDA MIDWIFE CLINIC IN LIDANG, PANYABUNGAN DISTRICT, MANDAILING NATAL REGENCY YEAR 2023 - Tinendung, Dewi SriRahayu (International Journal of Medicine And publich Health, 2024)
Anemia in pregnancy is a condition of pregnant women with hemoglobin levels below 11gr%. caused by the large number of women who start pregnancy with insufficient food reserves. During pregnancy iron is needed for the formation of red blood cells, fetus and placenta, where anemia in pregnancy is most often found anemia due to iron deficiency, this can be caused by the lack of inclusion of iron elements in the diet. Asphyxia is a condition of a newborn who experiences spontaneous and regular breathing failure immediately after birth, so that the baby cannot enter oxygen and cannot remove charcoal acid substances from his body. This study aims to determine the Relationship of Anemia During Pregnancy to the Incidence of Partus with Complications in the Occurrence of Asphyxia in Newborns at the Nurmalinda Dalan Lidang Midwife Clinic, Panyabungan District, Mandailing Natal Regency in 2023. The type of research used is descriptive research with a cross sectional approach The population in the study is the mother who checks her pregnancy at the nurmalinda clinic . The type of research used is descriptive research with a cross sectional approach The population in the study is the mother who checks her pregnancy at the nurmalinda clinic . The sampling technique uses Total Sampling with a sample size of 36 people. Data collection by using primary and secondary data. Data analysis using the chi -square test had an association of anemia during pregnancy to the incidence of partus with complications of asphyxia with a value of P = 0.034 where P = <0.05. It is hoped that pregnant women will increase their concern for anemia during pregnancy by consuming Fe tablets, being present in every counseling held by health workers, paying attention to every education health to understand the benefits and side effects of taking Fe tablets so that the mother remains healthy during pregnancy and avoids anemia.